Values and Organizational Commitment of employed in Durango City - Hernández Vela, Hortensia (Universidad de Sonora, 2020)
Organizations are interested in organizational commitment because it has been related to personal retention, performance, productivity and loyalty, this commitment on the other hand can in turn be relatedto the personal values of employees regardless of the organization in this Research is intended to identifythe type and degree of commitment of employees in relation to their values. The results indicate differences in the type of commitment and although the same values are identified, they do not present the same priority.